2021
DOI: 10.1002/agj2.20788
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DSSAT‐CROPGRO‐cotton model to simulate phenology, growth, and seed cotton yield in northwestern India

Abstract: Crop simulation models are widely used in developed countries to understand the impact of uncertain weather situations on crop production and consequent strategies formulation but their application in developing countries like India is limited and thus needs to be strengthened. The main objective of this study was to evaluate the DSSAT-CROPGRO-cotton (Gossypium hirsutum L.) model for assessing impact of varying weather on productivity dynamics of cotton in northwestern India. To ascertain this, field experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Besides better fruiting structures, Bt cultivars also possessed the quality of producing higher total dry matter over non Bt cultivars (Joshi et al 2011). Higher seed cotton yield for Bt cotton hybrids has been evident in accordance with findings of Mishra et al (2021) who reported better yield contributing parameters such as more bolls per plant and bigger boll size to be primary reason for superiority of transgenic cultivars over conventional varieties.…”
Section: Resultssupporting
confidence: 85%
“…Besides better fruiting structures, Bt cultivars also possessed the quality of producing higher total dry matter over non Bt cultivars (Joshi et al 2011). Higher seed cotton yield for Bt cotton hybrids has been evident in accordance with findings of Mishra et al (2021) who reported better yield contributing parameters such as more bolls per plant and bigger boll size to be primary reason for superiority of transgenic cultivars over conventional varieties.…”
Section: Resultssupporting
confidence: 85%
“…Biomass accumulation was measured by cutting the whole aboveground portion of the plant after harvest and then weighing after thorough drying under the sun. SCY constituted the total weight of both the hand pickings and is expressed in kilograms per hectare ( Mishra et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This necessitates the adoption of improved and efficient water application strategies to increase the crop productivity with better irrigation management ( Fernández et al., 2020 ; Mishra et al., 2021 ). To achieve food and fiber security for the ever-increasing population, a globally irrigated agricultural area needs to be increased by 20%, with about 40% increase in irrigated crop yield by year 2025 ( Hashem et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that the average error of phenological development time simulated by calibrated CROPGRO-Cotton in southern Xinjiang is 2.52% [48], which is close to the simulation accuracy of this study. Other research results show that calibrated CROPGRO-Cotton fairly predicts phenological events such as anthesis and physiological maturity with RMSE of ≤2.27 and ≤4.98 d, respectively, in northwestern India [49], and absolute relative errors of 1.7%, 1.1%, and 1.1% based on modified CROPGRO-Cotton. These differences might result from the effects of cotton cultivar and cultivation.…”
Section: Simulation Performance Analysis Of the Calibrated Wofost Mod...mentioning
confidence: 89%